HUBUNGAN PAJAK DAN ZAKAT MENURUT PERSPEKTIF ISLAM - Edi Haskar (Menara Ilmu, 2020)
In many countries, tax is one of the main foreign exchange earners in supporting national development so that it becomes a collection that has logical consequences in living as a society, nation and state as a reflection of justice and prosperity. Taxes are imposed on every citizen who has the obligation to pay taxes. In the teachings of Islam there are groups of people who are obliged to spend a small portion of their wealth as zakat, ie those who have been categorized as able to give alms. Zakat means to issue a certain amount of assets owned to be given to people who are entitled to receive it, materially zakat can create economic growth for people poor people. Called zakat because it contains hope to obtain blessings, cleanse the soul and cultivate it with various virtues, zakat can also foster cleanliness and blessing on possessions. During the time of Rasulullah and Khulafaurrosidin Zakat was imposed on residents who were Muslim, while taxes were imposed on non-Muslim residents, so that no population was affected by the dual obligation of zakat and tax. Basically, the purpose of tax and zakat is the same, namely as a source of funds to create a just and prosperous society that is equitable and sustainable between material and spiritual needs. Basically, taxes are used to finance activities in the development sector and sector, as well as the distribution of zakat to mustahik, especially the poor and the poor, is expected to support economic life so that it can help national economic development. Keywords: Tax, zakat, Islamic law.